Mussel-Inspired Modification of Nanofibers for REST siRNA Delivery: Understanding the Effects of Gene-Silencing and Substrate Topography on Human Mesenchymal Stem Cell Neuronal Commitment - Low, Wei Ching (2015)
In this study, we promote neuronal differentiation of human mesenchymal stem cells (MSCs) through scaffold-mediated sustained release of siRNA targeting RE-1 silencing transcription factor (REST). Poly (ϵ-caprolactone) nanofibers were surface modified with mussel inspired DOPA-melanin (DM) coating for adsorption of REST siRNA. DM modification increased siRNA-loading efficiency and reduced the initial burst release. Fiber alignment and DM modification enhanced REST knockdown efficiencies. Under non-specific differentiation condition, REST silencing and fiber topography enhanced MSC neuronal markers expressions and reduced glial cell commitment. Such scaffolds may find useful applications in enhancing MSCs neuronal differentiation under non-specific conditions such as an in vivo environment.